Development of multimedia learning educational game based for teachers SMP N 3 Sungai Kakap - Danar Santoso; Chandra Lesmana (Sean Institute, 2024)
This research aims to determine the feasibility of Educational Game-Based Multimedia Learning at SMP 03 Sungai Kakap. The method used in this research is a Research and Development method with the ADDIE model design (Analysis, Design, Development, Implementation and Evaluation). The product trial subjects in this research were Class VII Students at SMP Negeri 3 Sungai Kakap in the Mathematics subject. The data collection techniques used are observation, direct communication techniques and indirect communication. The conclusion that can be drawn is that the feasibility of Game-Based Learning media using the Construct2 Application in mathematics subjects in class VII of SMP Negeri 3 Sungai Kakap is known in terms of media and material to be classified as